The Effect of Rehabilitation Games on Sustained Attention in University Students: A Randomized Clinical Trial - Yazdan Movahedi; Abbas Mousivand; Mahdi Pourjafar (Vesnu Publications, 2020)
Introduction:Filial therapy is an effective strategy dealing with cognitive disorders. The aim of this study is to investigate the impact of rehabilitation computer games on increasing sustained attention in university students. Materials and Methods: In this randomized clinical trial, the target population consisted of students in Islamic Art University of Tabriz, Iran, in 2019 among who 30 students were selected with convenience sampling and divided randomly into two groups of 15 each by lot. 15 subjects played the rehabilitation games and the remaining 15 ones in the control received no intervention. The data were analyzed by multivariate analysis of covariance (ANCOVA). Results: Data analysis showed that there was a significant difference between the pre-test and post-test scores of the experimental and control groups (P < 0.04), indicating that the rehabilitation game has improved the level of attention (P ≤ 0.02). Conclusion: This study shows that rehabilitation games can be used as an effective method in individuals to increase attention.